Approaches and values in two gigantic educational philosophies: East and West - Hassan, Aminuddin; Jamaludin, Nur Syuhada (School of Education, Durham University, 2010)
The idea and the notion of philosophy of education has been derived traditionally and modernly, became combined and simultaneously work on each other, in order to produce the supreme culture of education to the humanity. Discussing on this discipline, there are numerous aspects that are not parallel with each other, whenever comparing these aspect within the understanding of education itself, through the countries apart of this global nation. Thus, this paper attempts to perceive the approaches and the values in two gigantic educational philosophies, which are education system from the West and East. The culture and tradition of the society itself had shaped in development of both philosophies, revealed how far these disciplines are contrast to each other. This paper will look on the comparison between Western and Eastern Education Philosophies from the aspect of students involvement within classroom activity, the technique of teaching and learning process, the expression of learning process, the capability of students for both philosophies, the encouragement for the students, and the relationship between the teachers and the students. This paper also will look on the appraisal towards Western and Eastern Philosophies, and at last will look on the educational system of Malaysia from the views of Western and Eastern Educational Philosophies, along with the implication and suggestion through the practice of both philosophies.